IMPACT OF CORPORATE GOVERNANCE ON CSR DECOUPLING: EVIDENCE FROM UK FTSE 350 NON-FINANCIAL FIRMS - Rumbidzai Mukonoweshuro,; Mohammadnavid Fattahi Hassanabad,; Tafara Mukonoweshuro, (PEOPLE: International Journal of Social Sciences, 2026)
Corporate Social Responsibility (CSR) decoupling tends to have long-term negative financial and non-financial consequences that impacts the corporations and its stakeholders. This research study identifies the corporate governance characteristics that influence CSR decoupling of UK FTSE 350 non-financial companies. Data for the period from 2010 to 2021, was collected from Bloomberg and LSEG Workspace Databases for 147 UK FTSE 350 non-financial firms. Ordinary Least Squares (OLS) regression analysis in Python, was used to analyse the data and the results from the analysis were collected. The research findings suggest that board gender diversity, larger firm size and lower gearing have an impact on CSR decoupling. The environmental element of CSR decoupling measured by environmental score decoupling displays results that indicate board gender diversity, lack of sustainability committee, lower return on assets and low gearing, have an impact on environmental score decoupling. These results suggest that board gender diversity has influence on CSR decoupling and environmental score decoupling and exacerbates both. This research suggests that optimal board gender diversity can be an interventional tool to control CSR decoupling while, the presence of sustainability committee is additionally vitally required to resolve and manage the environmental score decoupling. Practically, the UK Corporate Governance Code framework could adopt measures for effective corporate boards which curbs and enhances CSR practices. Various stakeholders can persuade companies to adopt useful corporate board attributes to safeguard and reduce decoupling shortcomings.